Improvement of the anticancer efficacy of PD-1/PD-L1 blockade via combination therapy and PD-L1 regulation - Wu, Mengling; Huang, Qianrui; Xie, Yao; Wu, Xuyi; Ma, Hongbo; Zhang, Yiwen; Xia, Yong (Journal of hematology and oncology, 2022)
Immune checkpoint molecules are promising anticancer targets, among which therapeutic antibodies targeting the PD-1/PD-L1 pathway have been widely applied to cancer treatment in clinical practice and have great potential. However, this treatment is greatly limited by its low response rates in certain cancers, lack of known biomarkers, immune-related toxicity, innate and acquired drug resistance, etc. Overcoming these limitations would significantly expand the anticancer applications of PD-1/PD-L1 blockade and improve the response rate and survival time of cancer patients. In the present review, we first illustrate the biological mechanisms of the PD-1/PD-L1 immune checkpoints and their role in the healthy immune system as well as in the tumor microenvironment (TME). The PD-1/PD-L1 pathway inhibits the anticancer effect of T cells in the TME, which in turn regulates the expression levels of PD-1 and PD-L1 through multiple mechanisms. Several strategies have been proposed to solve the limitations of anti-PD-1/PD-L1 treatment, including combination therapy with other standard treatments, such as chemotherapy, radiotherapy, targeted therapy, anti-angiogenic therapy, other immunotherapies and even diet control. Downregulation of PD-L1 expression in the TME via pharmacological or gene regulation methods improves the efficacy of anti-PD-1/PD-L1 treatment. Surprisingly, recent preclinical studies have shown that upregulation of PD-L1 in the TME also improves the response and efficacy of immune checkpoint blockade. Immunotherapy is a promising anticancer strategy that provides novel insight into clinical applications. This review aims to guide the development of more effective and less toxic anti-PD-1/PD-L1 immunotherapies.